2014
DOI: 10.1093/ckj/sft162
|View full text |Cite
|
Sign up to set email alerts
|

Renal manifestations of tuberous sclerosis among children: an Indian experience and review of the literature

Abstract: ObjectiveThe objective of this study was to describe the renal manifestations in children 0–18 years of age diagnosed with tuberous sclerosis complex (TSC) at a tertiary hospital in South India.MethodsData of children with TSC, who presented to Christian Medical College Vellore Hospital from January 2008 to January 2013, were analysed by a retrospective chart review. The cases were identified from outpatient records and underwent ultrasonography, urine analysis and examination of serum creatinine to recognize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Similarly, the 43% rate of angiomyolipomas in this study is comparable to the 40% to 80% previously reported. 34,40 The rate of renal cysts in our study, 19%, is at the low end of the 17% to 47% rate reported in these studies. Although typically asymptomatic in childhood, these lesions tend to increase in size over time and can lead to hypertension, hemorrhage, and end-stage renal disease.…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, the 43% rate of angiomyolipomas in this study is comparable to the 40% to 80% previously reported. 34,40 The rate of renal cysts in our study, 19%, is at the low end of the 17% to 47% rate reported in these studies. Although typically asymptomatic in childhood, these lesions tend to increase in size over time and can lead to hypertension, hemorrhage, and end-stage renal disease.…”
Section: Discussioncontrasting
confidence: 56%
“…Renal lesions serve an important role in the course of TSC by impairing renal function ( 29 ). Renal cysts, angiomyolipomas and renal cell carcinomas are the most common renal lesions in patients with TSC ( 30 , 31 ). Isaacs ( 32 ) reported that 13.2% of neonates and fetuses with TSC exhibit renal cysts.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] One of them had a unifying diagnosis of tuberous sclerosis. [3] These articles suggest that one should look for renal involvement in patients with tuberous sclerosis complex (TSC).…”
Section: Discussionmentioning
confidence: 99%
“…[3] These articles suggest that one should look for renal involvement in patients with tuberous sclerosis complex (TSC). [2][3][4] Could this patient have TSC, or could the angiomyolipoma be unusual renal metastases presenting radiologically as angiomyolipoma? [5] Could her freckles be mistaken for angiofibromas, which would support the diagnosis of tuberous sclerosis?…”
Section: Discussionmentioning
confidence: 99%